HAKIKAT DAN FILSAFAT ILMU KRIPTOGRAFI - Rizki Ariyani (Asosiasi Dosen Muda Indonesia, 2022)
The foundation of a science is a fundamental thing that must be known. The essence of a science is the foundation of that science. The essence and philosophy are interconnected in knowledge, so in a science, the origins of the development of knowledge can be understood. The science that is currently developing is certainly driven by the nature and philosophy of that science, which serves as the basis for research development. Cryptography is one of the sciences developed based on mathematics applied to the security of communication. Cryptography currently encompasses the security of communication in information technology. The discussion of this research is about the thoughts and opinions from the literature related to the nature and philosophy of cryptography, its history, development, and its application as security in information technology.